Grain weight and seedling vigor in diploid and teraploidryes (Semiárida, 2020)
The objetives of this study were to determine the influence of seed weight and ploidy level on rye seedling vigor. Three seed weight and two ploidy levels were evaluated in blotting paper sandwich. Data were subjeted to analysis of variance and LSDs were calculated. Seedling vigor measured as green biomass, leaf blade length and seedling diameter increased with seed weight and ploidy level. Also the leaf blade length and coleoptile length increased with seed weight. Dry matter percentage decreased as the ploidy level increased.
Keywords: grain weight; seedling vigor; rye; ploidy level